2014
DOI: 10.1007/s10266-014-0164-3
|View full text |Cite
|
Sign up to set email alerts
|

Formation and development of maxillary first molars with delayed eruption

Abstract: Cases of congenitally missing and delayed eruption of the maxillary first molar are rare. However, in recent years, we have experienced cases of suspected delayed eruption of or congenitally missing first molars. The purpose of this study was to analyze the formation of delayed erupted maxillary first molars (M1) (>2 standard deviations), which play important roles in occlusion, and normal eruption of the maxillary first molars (U6). The frequency of M1 among patients born between 1974 and 1994 in one institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 22 publications
2
6
1
Order By: Relevance
“…In the Japanese population, 98.0% to 100.0% of the maxillary first molars have four cusps, whereas 60.2% to 64.2% of the maxillary second molars have four cusps [35][36][37]. More cases of the maxillary molars with delayed eruption were collected from females than from males in our previous study [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Japanese population, 98.0% to 100.0% of the maxillary first molars have four cusps, whereas 60.2% to 64.2% of the maxillary second molars have four cusps [35][36][37]. More cases of the maxillary molars with delayed eruption were collected from females than from males in our previous study [14].…”
Section: Discussionmentioning
confidence: 99%
“…Subjects in the current study were selected from patients visiting an orthodontic clinic in Nagaoka City, Niigata Prefecture, Japan who met the following criteria: eruption of the maxillary first molar delayed by more than 1.3 years (two SD later than average eruption of maxillary first molars in Japanese females (6.58 ± 0.67 years) [13]; no ectopic eruption or odontoma; and no systemic diseases including cleft lip, jaw or palate [14]. A total of 73 Japanese patients (20 males and 53 females) were enrolled in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Delayed development and eruption of the U6 may result in unstable occlusion, which can negatively affect oral function ( Proff et al, 2006 ). Several studies have reported the delayed U6 development and eruption in the absence of physical obstacles, while the development and eruption of permanent mandibular first molars occurred normally ( Rasmussen, 1998 , Nakano et al, 1999 , Sano et al, 2010 , Sano et al, 2015 , Klein et al, 2016 , Lee et al, 2017 ). Rasmussen (1998) was the first to describe 10 cases of delayed eruption of permanent first molars, which were delayed until around age nine.…”
Section: Introductionmentioning
confidence: 99%
“… Sano et al (2010) evaluated 51 Japanese children with delayed U6 eruption and found that the average delayed eruption time was 2.09 years in males and 2.84 years in females ( Sano et al, 2010 ). A study by the same author reported that the prevalence of delayed U6 eruption from 2001 panoramic radiographs obtained from 73 patients was 1.55%, with bilateral occurrence in 80% of cases and a male-to-female ratio of 1:2.65 ( Sano et al, 2015 ). A study at the University of Colorado reported the prevalence of delayed U6 eruption in 13,140 children to be 0.4%, with an average delayed eruption time of 2.48 years in males and 2.93 years in females, and a male-to-female ratio of 1:2.1 ( Klein et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the data of scientific literature show that in recent years there has been an increasing interest in the laws of the development of the jaw system components [2; 18; 22; 26; 29; 32]. The processes of the formation and development of jaws and teeth have attracted the attention of many researchers [25].…”
mentioning
confidence: 99%